Absorção de fósforo, nitrogênio e potássio pelas hortaliças em um sistema aquapônico - Aquino Junior, Francisco de Assis Medeiros de (Universidade Federal Rural do Semi-Árido, 2019)
Aquaculture has proven to be an alternative source for good quality food, but this activity generates a high amount of waste that decreases water quality, causing pollution through the discharge of water and high consumption of water. In addition, traditional farming systems occupy considerable areas of land, which makes this activity very costly. In order to minimize these problems, the recirculation system was created, in which the water of the crop is reused almost completely, allowing a higher stocking density, thus reducing waste, increasing the preservation of the environment and reducing the cultivation areas. This type of system was optimized with the association of hydroponics to the same, allowing the production of vegetables and fish simultaneously in a sustainable way. Thus, fish generate nutrients that will be absorbed by the plants, which use them for their development, thus reducing the amount of these in the medium, which will provide better quality water for fish farming. This study was developed in the aquaculture sector of the Federal Rural Semi-Arid University (UFERSA), located on the campus of Mossoró in Rio Grande do Norte. A NFT (nutrient film technique) type aquaponic system with 15 tilapias (Oreochromis niloticu) with an average initial weight of 155.7 g was stored in a 500-L water box. Cinderella lettuce (Lactuca sativa) and Coriander Verdão (coriandrum sativum L.) were cultivated in PVC pipes without substrate. The vegetables were harvested and taken for analysis to determine the content of P, N and K absorbed by them. Three water samples were collected at the exit of the plants and the other in the mechanical filter for analysis of P, N and K in the culture medium. The experiment was carried out in 87 days, from the storage of the fish in the growing box to the harvest of the vegetables. In this context, the objective of this work was to quantify the production and absorption of nutrients nitrogen, phosphorus and potassium in the cultivation of fish and vegetables in an aquaponic system. The lettuce had a content of 28.0, 7.16 and 33.29 g. kg-1 of N, P and K respectively, while the coriander recorded 27.56, 3.95 and 19.21 g. kg-1 of N, P and K respectively, showing that fish produce sufficient quantities of these nutrients for the development of vegetables. All the analyzed nutrients showed a decrease in the three water samples, in the comparative analysis of N, P and K, between the three samples both in the water of the plants and in the water of the filter, did not present significant differences (P> 0.05). Thus, residual water from fish culture can provide N, P and K sufficient for the production of lettuce and coriander in an aquaponic system, making fertilization and fertilization of these vegetables unnecessary with commercial products.
Monografia
Keywords: Aquaponia; Cultivo; Hortaliças; Nutrientes; Peixes; CIENCIAS AGRARIAS::RECURSOS PESQUEIROS E ENGENHARIA DE PESCA